Holey MoS2 Nanosheets with Photocatalytic Metal Rich Edges by Ambient Electrospray Deposition for Solar Water Disinfection. Issue 12 (10th September 2018) - Sarkar, Depanjan; Mondal, Biswajit; Som, Anirban; Ravindran, Swathy Jakka; Jana, Sourav Kanti; Manju, C. K.; Pradeep, Thalappil
Abstract: A new method for creating nanopores in single‐layer molybdenum disulfide (MoS2 ) nanosheets (NSs) by the electrospray deposition of silver ions on a water suspension of the former is introduced. Electrospray‐deposited silver ions react with the MoS2 NSs at the liquid–air interface, resulting in Ag2 S nanoparticles which enter the solution, leaving the NSs with holes of 3–5 nm diameter. Specific reaction with the S of MoS2 NSs leads to Mo‐rich edges. Such Mo‐rich defects are highly efficient for the generation of active oxygen species such as H2 O2 under visible light which causes efficient disinfection of water. 10 5 times higher efficiency in disinfection for the holey MoS2 NSs in comparison to normal MoS2 NSs is shown. Experiments are performed with multiple bacterial strains and a virus strain, demonstrating the utility of the method for practical applications. A conceptual prototype is also presented. Abstract : A new method for creating nanopores in single‐layer molybdenum disulfide (MoS2 ) nanosheets (NSs) by the electrospray deposition of silver ions is introduced. Specific reaction with the S of MoS2 NSs leads to Mo‐rich edges. Such Mo‐rich defects are highly efficient for the generation of active oxygen species such as H2 O2 under visible light which causes efficient disinfection of water.